Career directions handbook - Yena, Donna J. (New York : McGraw-Hill, 2011)
Career Directions The Path to Your Ideal Career, provides diverse job seekers with the essential resources and techniques to develop a career plan, conduct a successful job search, and succeed in a diverse workplace. Whether your students are seeking an internship or co-op job, first position after graduation, or a career transition, "Career Directions" will prepare students to stand out in the changing workplace! Students in career schools, colleges, community colleges, and universities can all benefit from using this book in career development courses and career workshops.
Includes index
Keywords: Vocational guidance